2009
DOI: 10.1253/circj.cj-07-1016
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Prognosis of Chronic Heart Failure Reduced vs Preserved Left Ventricular Ejection Fraction

Abstract: Background Left ventricle diastolic dysfunction is attracting increasing attention of one of the etiologies of chronic heart failure (CHF). Methods and ResultsThe study sample included 560 patients with CHF who were hospitalized during the 5-year period. They were classified into 2 groups according to the left ventricular ejection fraction (LVEF): reduced group (LVEF <50%, n=431); or preserved group (LVEF ≥50%, n=129). The degree of cardiac symptoms did not differ between the 2 groups; however, no difference w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 38 publications
5
11
0
3
Order By: Relevance
“…Data regarding this is limited. A recent study showed that the cause of death was due to heart failure in 46% of these patients, a percentage that was not significantly different from patients with reduced function [24]. Although the clinical characteristics of patients with preserved LVF are quite distinct from patients with reduced LVF, the clinical syndromes are very similar.…”
Section: Discussionmentioning
confidence: 93%
“…Data regarding this is limited. A recent study showed that the cause of death was due to heart failure in 46% of these patients, a percentage that was not significantly different from patients with reduced function [24]. Although the clinical characteristics of patients with preserved LVF are quite distinct from patients with reduced LVF, the clinical syndromes are very similar.…”
Section: Discussionmentioning
confidence: 93%
“…There is growing recognition that among patients with clinical syndromes associated with heart failure, approximately half have preserved left ventricular systolic function, known as heart failure with preserved ejection fraction (HFpEF) [1]. Clinical evidence suggests that the morbidity and mortality rates associated with HFpEF are high and almost equal to those associated with heart failure with reduced ejection fraction (HFrEF) [2]. Recent clinical studies have provided sufficient data to help develop standardized diagnostic criteria to define HFpEF [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that patients in normal left ventricular ejection fraction group and lower left ventricular ejection fraction group have similar prognosis in previous epidemiological investigations and observational studies [20]. But most of those experiment objects have dilated cardiomyopathy, and hypertensive heart disease patients take low proportion in patients with CAD.…”
Section: Discussionmentioning
confidence: 85%